Redefining American conservation for equitable and inclusive social‐environmental management. Issue 1 (30th November 2022) - Morales, Nia; Lee, Jordan; Newberry, Milton; Bailey, Karen
Abstract: Efforts to recruit, retain, and include Blacks, Indigenous, and People of Color (BIPOC) in environmental fields often fall short, in part due to limited conceptualizations of conservation and environment. At the core of this is the North American Model for Wildlife Conservation, an important approach to conservation and wildlife management that has influenced conservation globally. This model, however, is based upon a specific subset of worldviews, driven by Western and Eurocentric constructions of wilderness and nature. This model creates a narrow view of human–environment relationships and erases cultures and communities that explicitly view themselves as part of nature. We review the seven tenets of the North American Model for Wildlife Conservation, highlighting their limitations and exclusion of other models of environmental and natural resource management and alternative relationships with nature. In order to support long‐term environmental engagement and culturally responsive research, 21st century environmental practitioners should shift our thinking around conservation to center counter narratives of BIPOC communities, scientists, and professionals as part of and meaningfully connected to nature. We argue that relying solely on the historically dominant language and ideologies at the core of the North American Model perpetuates disparities in environmental engagement and limits retention of BIPOC in environmental fields. We further highlight how shifts in understanding conservation and relationships to nature enables us to re‐frame our work to support equitable, inclusive, and just conservation science and practice.